A new Microhyla species (Anura: Microhylidae) from riparian evergreen forest in the eastern Himalayan state of Arunachal Pradesh, India - Biju, S. D.; Garg, Sonali; Kamei, Rachunliu G.; Maheswaran, Gopinathan (Zootaxa, 2019)
A new frog species of the genus Microhyla (Anura, Microhylidae) is described from riparian mid-elevation (860 m asl) evergreen forest in Namdapha National Park, located in the eastern Himalayan state of Arunachal Pradesh, India. The new species can be morphologically distinguished from other congeners by a suite of characters such as adult size, dorsal and lateral colouration and markings, snout shape, foot webbing, and digit tip morphology. Phylogenetically, the new species is more closely related to some of the smallest known members of the genus. It forms a deeply divergent sister lineage to the clade containing members of the Microhyla zeylanica species group that are restricted to Peninsular India and Sri Lanka, and shows sequential relationship with Southeast Asian species M. superciliaris, followed by clade containing M. aurantiventris + M. butleri. The discovery indicates that novel taxa representing distinct evolutionary lineages still remain to be formally described in the genus Microhyla, especially from less explored regions such as the eastern Himalayan forests in Northeast India.